2015
DOI: 10.1111/pce.12467
|View full text |Cite
|
Sign up to set email alerts
|

OsAUX1 controls lateral root initiation in rice (Oryza sativaL.)

Abstract: Polar auxin transport, mediated by influx and efflux transporters, controls many aspects of plant growth and development. The auxin influx carriers in Arabidopsis have been shown to control lateral root development and gravitropism, but little is known about these proteins in rice. This paper reports on the functional characterization of OsAUX1. Three OsAUX1 T-DNA insertion mutants and RNAi knockdown transgenic plants reduced lateral root initiation compared with wild-type (WT) plants. OsAUX1 overexpression pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(84 citation statements)
references
References 94 publications
(186 reference statements)
3
81
0
Order By: Relevance
“…Auxin redistribution is mainly controlled by auxin transporters, which include the influx transporters of the AUXIN1/LIKE AUX1 (AUX1/LAX) family (Kerr and Bennett, 2007; Swarup et al, 2008; Zhao et al, 2015), and efflux transporters of the PIN-FORMED (PIN) families (Petrasek et al, 2006; Wang et al, 2009). To test how ABA signaling regulates auxin transport, we investigated the ABA-regulated expression of the major genes involved in auxin transport.…”
Section: Resultsmentioning
confidence: 99%
“…Auxin redistribution is mainly controlled by auxin transporters, which include the influx transporters of the AUXIN1/LIKE AUX1 (AUX1/LAX) family (Kerr and Bennett, 2007; Swarup et al, 2008; Zhao et al, 2015), and efflux transporters of the PIN-FORMED (PIN) families (Petrasek et al, 2006; Wang et al, 2009). To test how ABA signaling regulates auxin transport, we investigated the ABA-regulated expression of the major genes involved in auxin transport.…”
Section: Resultsmentioning
confidence: 99%
“…In Arabidopsis , the AUX1 and LIKE‐AUXIN3 (LAX3) auxin influx carriers are required for auxin signalling activating LBD16 and LBD18 (lateral organ boundaries domain [LBD]) to control LR development (Lee, Cho, & Kim, ). In rice, the osaux1 mutant has a reduced number of LR primordia (Zhao et al, ). In osaux3‐2 , all these feature including delayed LR initiation, decreased LR primordia, reduced LR density, and decreased expression of genes related to LR initiation suggest that OsAUX3 plays an important role during LR initiation, which would be consistent with a conserved function to its homologues/analogues, AtAUX1, AtLAX3, or OsAUX1 (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…In rice, there are five members of the AUX1/LAX family (Shen et al, ). OsAUX1 was reported to function in regulation of LR development (Zhao et al, ). Previously, we have shown that OsAUX1 , besides negatively regulating primary root (PR) elongation, positively regulates root hair (RH) development and responds to Cd stress (Yu et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…PaLAX1 , from wild cherry ( Prunus avium ), promotes the absorption rate of auxin in cells and affects the distribution of free endogenous auxin [20]. OsAUX1 controls the lateral root initiation, primary root and root hair elongation in rice [21, 22]. In sorghum , maize ( Zea mays ) and soybean (Glycine max), some AUX/LAX genes are in response to hormonal and abiotic stress at transcriptional level [2325].…”
Section: Introductionmentioning
confidence: 99%